2017
DOI: 10.1108/pijpsm-06-2016-0077
|View full text |Cite
|
Sign up to set email alerts
|

Police legitimacy in context: an exploration of “soft” power in police custody in England

Abstract: Purpose-The purpose of this paper is to examine how police authorityin its "soft" formis used and understood by staff and detainees in police custody in England, examining how these meanings are shaped by this unique police setting. It is argued that the nature of this setting, as fraught and uncertain, along with the large volume of citizens who come into contact with the police therein, makes police custody the ultimate "teachable moment". Design/methodology/approach-The present paper is based on in-depth qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…These findings showed that ‘good’ police custody is something more than the use of soft skills [ 65 ]. Although beyond the direct aim of this study, it is safe to infer that the tensions identified by police custody officers and police staff in the current study could be resolved by creating a national police custody service staffed by police custody inspectors/managers and sergeants seconded for the purpose (as in other branches of the service like regional police training), who would continue to be supported by civilian detention officers/assistants and nurses.…”
Section: Discussionmentioning
confidence: 99%
“…These findings showed that ‘good’ police custody is something more than the use of soft skills [ 65 ]. Although beyond the direct aim of this study, it is safe to infer that the tensions identified by police custody officers and police staff in the current study could be resolved by creating a national police custody service staffed by police custody inspectors/managers and sergeants seconded for the purpose (as in other branches of the service like regional police training), who would continue to be supported by civilian detention officers/assistants and nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found the DOs with whom the arrestees have the most frequent contact are adept in interpersonal interactions within this context of containment; providing credibility and skills that are considered necessary to navigate this setting. This has been found in other research into police custody detention officers, who have been found to be skillful in the use of 'soft power', wherein detention officers were able to build rapport with arrestees by distinguishing themselves from the arresting officer, communicating respect and the use of humour (Skinns et al, 2016). However DOs were found to lack confidence and taskspecific self-esteem in providing a caring intervention in response to the identified need.…”
Section: Discussionmentioning
confidence: 65%
“…Whilst workload pressure and competing demands have been highlighted as an issue in other settings (Anderson, 2009;Bendtsen et al, 2015;Brown, Newbury-Birch, McGovern, Phinn, & Kaner, 2010) and have been associated with poor implementation of alcohol screening and brief intervention (Wilson et al, 2011), these settings have a primary function of providing care. Within the custody suite, care other than that with immediate and urgent consequence, is at times viewed as being in conflict with the core function of containment, with research finding an inverse relationship between the levels of busyness within different custody suites and how 'good' policing is for the arrestee (Skinns, Rice, Sprawson, & Wooff, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in geography drawing on liminality have tended to focus on sites that are fixed, ongoing and usually building-based (Atkinson & Robson, 2012). A small number of geographers, and others in related disciplines, have detailed the role of physical and emotional spaces in shaping experiences of liminality, including the police custody cell (Skinns et al, 2017), end-of-life care (Marsh et al, 2017), and the internet (Madge & O'Connor, 2005). Feminist geographers have long critiqued the power-laden and constraining duality of private and public space, and highlighted the presence and vitality of spaces in-between, often occupied by women and others, including people with disability (e.g., Jang et al, 2019) who are socio-spatially marginalised.…”
Section: Liminal Space and Timementioning
confidence: 99%